2006
DOI: 10.1002/neu.20333
|View full text |Cite
|
Sign up to set email alerts
|

The molecular receptive range of an olfactory receptorin vivo(Drosophila melanogasterOr22a)

Abstract: Understanding how odors are coded within an olfactory system requires knowledge about its input. This is constituted by the molecular receptive ranges (MRR) of olfactory sensory neurons that converge in the glomeruli of the olfactory bulb (vertebrates) or the antennal lobe (AL, insects). Aiming at a comprehensive characterization of MRRs in Drosophila melanogaster we measured odor-evoked calcium responses in olfactory sensory neurons that express the olfactory receptor Or22a. We used an automated stimulus appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 66 publications
(125 reference statements)
6
96
3
Order By: Relevance
“…Notably, experiments within the same study (Oka Y et al, 2006) have shown that whereas delivery of the odorant as a vapor still needs to reach μM concentrations when the response is measured at the cell level (e.g., HEK293 or isolated olfactory sensory neurons: OSNs), it only needs to reach nM concentrations when the response is measured at the glomerular level. Thus, responses measured beyond the individual cell level, be it at the olfactory bulb (mouse) (Oka Y et al, 2006), the antennal lobe (fly) (Pelz D et al, 2006), or the integrated olfactory system (human) (this study; Cain WS et al, 2007b;Cometto-Muñiz JE et al, 2004;Wise PM et al, 2007), produce EC 50 s at or below the nM range. In terms of concentration span, the odorant response often rises from background to maximum within approximately two log units of concentration but this span can vary from one {e.g., (Kajiya K et al, 2001)} to three {e.g., (Abaffy T et al, 2006)} log units, irrespective of stimulus phase (liquid or vapor) or level at which the olfactory path is probed.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 95%
See 2 more Smart Citations
“…Notably, experiments within the same study (Oka Y et al, 2006) have shown that whereas delivery of the odorant as a vapor still needs to reach μM concentrations when the response is measured at the cell level (e.g., HEK293 or isolated olfactory sensory neurons: OSNs), it only needs to reach nM concentrations when the response is measured at the glomerular level. Thus, responses measured beyond the individual cell level, be it at the olfactory bulb (mouse) (Oka Y et al, 2006), the antennal lobe (fly) (Pelz D et al, 2006), or the integrated olfactory system (human) (this study; Cain WS et al, 2007b;Cometto-Muñiz JE et al, 2004;Wise PM et al, 2007), produce EC 50 s at or below the nM range. In terms of concentration span, the odorant response often rises from background to maximum within approximately two log units of concentration but this span can vary from one {e.g., (Kajiya K et al, 2001)} to three {e.g., (Abaffy T et al, 2006)} log units, irrespective of stimulus phase (liquid or vapor) or level at which the olfactory path is probed.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 95%
“…Recent studies, particularly at the receptor level, have included olfactory concentrationresponse relationships (Abaffy T et al, 2006;Jacquier V et al, 2006;Kajiya K et al, 2001;Katada S et al, 2005;Oka Y et al, 2006;Pelz D et al, 2006;Shirokova E et al, 2005). Table 3 summarizes their characteristics and those of the present work.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined the Or22a receptor, which is sensitive to esters and alcohols (6,27). Responses of flies carrying a deletion that includes the Or22a gene and genetically matched controls (22,28) were tested to 23 odors.…”
Section: Consequences Of Losing Sensory Input From One Ormentioning
confidence: 99%
“…Responses of flies carrying a deletion that includes the Or22a gene and genetically matched controls (22,28) were tested to 23 odors. Of the odors tested, only the response to 1-heptanol, a weak agonist (27), was significantly reduced (Fig. 5A).…”
Section: Consequences Of Losing Sensory Input From One Ormentioning
confidence: 99%